The face bending behaviour of blind-bolted connections to concrete-filled hollow sections - Elamin, Ahmed Mohamed Elamin Ahmed (2014)
Structural Hollow Sections have superior structural performance over open sections and are currently available as circular, elliptical or rectangular sections. However, the practical use of these sections is limited due to complexities involved in their connections. The lack of access to the interior of the section makes it almost impossible to use standard bolted connections. The so-called Blind Bolts are therefore used as fasteners to alleviate these complexities by allowing for bolted rather than, the-not-so-popular, welded connections to hollow sections. Lindapter’s Hollo-Bolt is one of the Blind Bolts used for hollow sections connections. However its established use is currently restricted to transferring tensile forces and vertical shear only. Filling Square Hollow Sections (SHS) with concrete, when utilising Hollo-Bolts, was found to improve the connections’ performance in resisting moments, but there is currently no guidance available for the design of such connections.